2004
DOI: 10.1159/000080301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Individual and Family Functioning on Interest in Genetic Testing

Abstract: Objective: The present study reports on the important issue of how family communication and support regarding breast cancer risk affects interest in genetic testing and mental health. Methods: Participants (n = 221) were women aged 18–74 who had at least one relative of Ashkenazi Jewish descent, no personal history of breast or ovarian cancer, and lived within 60 miles of Seattle, Wash. Results: Communication about breast cancer risk was reported with very low frequency across all types of relatives. Women tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…34 Prior studies have found that lower social support at the time of testing may be associated with greater risk of both short-and long-term emotional distress. 62,63 To the extent that a decision regarding genetic testing is a difficult and stressful event, the active involvement of a highly supportive family may facilitate making such a choice.…”
Section: Discussionmentioning
confidence: 99%
“…34 Prior studies have found that lower social support at the time of testing may be associated with greater risk of both short-and long-term emotional distress. 62,63 To the extent that a decision regarding genetic testing is a difficult and stressful event, the active involvement of a highly supportive family may facilitate making such a choice.…”
Section: Discussionmentioning
confidence: 99%
“…These were reviewed in extenso. References [19,34,46,47,58,59,64,68,69,73,74,77,78] were combined by two or three when they were from the same center with the same target group, as indicated in the tables. Reference [79] provided background statistical data about Israel.…”
Section: Methods: Data Sources and Study Selectionmentioning
confidence: 99%
“…46 Frequency of communication with all listed first-and second-degree relatives was rated on a 4-point Likert scale, from 1 (not at all) to 4 (a lot). An option for ''I do not have a family member of this type or they are not living'' was provided.…”
Section: Outcome Measuresmentioning
confidence: 99%